2017
DOI: 10.1186/s13075-017-1230-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of arthritis and joint pain on individual healthcare expenditures: findings from the Medical Expenditure Panel Survey (MEPS), 2011

Abstract: BackgroundJoint pain, including back pain, and arthritis are common conditions in the United States, affecting more than 100 million individuals and costing upwards of $200 billion each year. Although activity limitations associated with these disorders impose a substantial economic burden, this relationship has not been explored in a large U.S. cohort.MethodsIn this study, we used the Medical Expenditures Panel Survey to investigate whether functional limitations explain the difference in medical expenditures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 26 publications
(23 reference statements)
2
16
0
Order By: Relevance
“…Improving function, either through enhancing body capacity to perform meaningful activities or through modifying the environment, was a main need perceived by the participants with arthritis in this study. This result aligns with what has been consistently reported in the worldwide literature, which shows that in comparison to the general population, people living with arthritis consistently experience higher rates of disability (29). The narratives from participants with arthritis express how disability is not only a result of losing the body's capacity to accomplish desire activities but also is conditioned by disabling environments that produce unsurmountable demands on their bodies, which limits the completion of meaningful activities and conditions hopelessness, anxiety and isolation.…”
Section: Improving Functionsupporting
confidence: 91%
“…Improving function, either through enhancing body capacity to perform meaningful activities or through modifying the environment, was a main need perceived by the participants with arthritis in this study. This result aligns with what has been consistently reported in the worldwide literature, which shows that in comparison to the general population, people living with arthritis consistently experience higher rates of disability (29). The narratives from participants with arthritis express how disability is not only a result of losing the body's capacity to accomplish desire activities but also is conditioned by disabling environments that produce unsurmountable demands on their bodies, which limits the completion of meaningful activities and conditions hopelessness, anxiety and isolation.…”
Section: Improving Functionsupporting
confidence: 91%
“…Different studies have reported significant economic burden of psoriasis, PsA, and AS in different countries,21–26 including Italy 27,28. The economic and humanistic burden of SpA is closely connected to the functional status in PsA and AS patients, and it is increased by the fact that SpA usually occurs in active young adults 7,29–33. According to a survey performed in 17 out of the 20 regions in Italy, sponsored by the National Association of Rheumatic Patients, half of the patients with SpA reported disability and one third felt that their condition limited their career progression and personal development 34…”
Section: Introductionmentioning
confidence: 99%
“…These results were not surprising because psoriatic disease is associated with a substantial economic burden, with costs around $135 billion annually in the United States alone 37 . Although data from the NPF indicate that 91% of patients with psoriatic disease have insurance coverage, out-of-pocket costs ranged anywhere from $2500 to $8000 in patients with psoriasis and PsA, with indirect costs accounting for 52% to 72% of total PsA costs 37,38,39,40 . Not surprisingly, increased costs are contributing to undertreatment of patients with psoriatic disease 41 .…”
Section: Rheumatologymentioning
confidence: 99%